The Impact of Kipalicu river for an environmental design development - Abrea, Antonietta C. (2004)
The research will study about the Kipalicu River. The river that is located along the Municipality of Kapalong, Davao del Norte. The study will have two major phases that is the research phase and the design development phase. The research phase includes the study on its biophysical features and the socioeconomic and cultural aspect of the community. The main objective of the study is to utilize the river and formulate a design concept for a design development, which included in the design phase. These objectives will give an alternative use of the river in addition to its existing use, which is for irrigation, household activities like washing of cloths and others; it is also used as waste disposal for animal manures and other waste products. This present situation gives an idea to include the awareness of the people with regard to the importance of the river and its impact to the human and its existing environment. Another concern of the research is the gradual lost of the culture of the original settlers mainly because of the social change that happen in the community and the migration that happen often times. The research will include the cultural aspect of the place that comprises their art and architecture for the preservation of the cultural distinct identity of Davaoenyo.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2005